Increased copy number of gibberellin 2‐oxidase 8 genes reduced trailing growth and shoot length during soybean domestication. (29th July 2021) - Wang, Xin; Li, Man‐Wah; Wong, Fuk‐Ling; Luk, Ching‐Yee; Chung, Claire Yik‐Lok; Yung, Wai‐Shing; Wang, Zhili; Xie, Min; Song, Shikui; Chung, Gyuhwa; Chan, Ting‐Fung; Lam, Hon‐Ming
Summary: Copy number variations (CNVs) play important roles in crop domestication. However, there is only very limited information on the involvement of CNVs in soybean domestication. Trailing growth and long shoots are soybean adaptations for natural habitats but cause lodging that hampers yield in cultivation. Previous studies have focused on Dt1/2 affecting the indeterminate/determinate growth habit, whereas the possible role of the gibberellin pathway remained unclear. In the present study, quantitative trait locus (QTL) mapping of a recombinant inbred population of 460 lines revealed a trailing‐growth‐and‐shoot‐length QTL. A CNV region within this QTL was identified, featuring the apical bud‐expressed gibberellin 2‐oxidase 8A/B, the copy numbers of which were positively correlated with expression levels and negatively with trailing growth and shoot length, and their effects were demonstrated by transgenic soybean and Arabidopsis thaliana . Based on the fixation index, this CNV region underwent intense selection during the initial domestication process. Significance Statement: Copy number variations (CNVs) play important roles in crop domestication. Two gibberellin 2‐oxidase 8 ( GA2ox8 ) genes in a CNV region within a quantitative trait locus under intensive selection were identified to suppress soybean shoot length and trailing growth phenotype and the physiological functions of these two GA2ox8 genes were validated by transgenic soybean and transgenic Arabidopsis thaliana .